Physical Condition Level of Futsal Players at Mts Masmur Pekanbaru: Tingkat Kondisi Fisik Pemain Futsal Di Mts Masmur Pekanbaru - Dela Musi Rais; Leni Apriani (Badnur Medisa Group, 2022)
This study was conducted to determine the level of physical condition of futsal players in futsal extracurricular at MTS Masmur Pekanbaru. The sample in this study was students who took part in futsal extracurricular at MTS Masmur Pekanbaru with 15 male futsal players. This type of research is a quantitative descriptive study, with the instruments used in the form of flexometer tests, vertical jumps, 50-meter runs, shuttle runs, 15-minute runs.Based on data processing carried out using a statistical system, there are less than 14 categories of people with a percentage (93,38%), less categories 0 people with a percentage (0%), good categories as much 1 person with a percentage (6,67%). Thus the average score of students on futsal extracurricular at MTS Masmur Pekanbaru is 3,09 which is classified as at intervals of 2.0 – 3.9, thus it can be said that the physical condition test that has been carried out at MTS Masmur Pekanbaru is classified as Less